A New Database on Financial Development and Structure - Levine, Ross, 1960- 16.04.1960- (The World Bank, 1999)
July 1999 - This new database of indicators of financial development and structure across countries and over time unites a range of indicators that measure the size, activity, and efficiency of financial intermediaries and markets. Beck, Demirgüç-Kunt, and Levine introduce a new database of indicators of financial development and structure across countries and over time. This database is unique in that it unites a variety of indicators that measure the size, activity, and efficiency of financial intermediaries and markets. It improves on previous efforts by presenting data on the public share of commercial banks, by introducing indicators of the size and activity of nonbank financial institutions, and by presenting measures of the size of bond and primary equity markets. The compiled data permit the construction of financial structure indicators to measure whether, for example, a country's banks are larger, more active, and more efficient than its stock markets. These indicators can then be used to investigate the empirical link between the legal, regulatory, and policy environment and indicators of financial structure. They can also be used to analyze the implications of financial structure for economic growth. Beck, Demirgüç-Kunt, and Levine describe the sources and construction of, and the intuition behind, different indicators and present descriptive statistics. This paper - a product of Finance, Development Research Group - is part of a broader effort in the group to understand the determinants of financial structure and its importance to economic development. The authors may be contacted at tbeck@worldbank.org, ademirguckunt@worldbank.org, or rlevine@csom.umn.edu